2013
DOI: 10.1002/macp.201300278
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerizable Monomer Miniemulsions: Why Does Droplet Size Matter?

Abstract: In monomer miniemulsions, droplet size is a key parameter impacting the optical properties, and consequently their photopolymerizability under UV light. Three simple spectrophotometric methodologies are developed, based on an integrating sphere, to evaluate precisely the effect of droplet size on radiation absorption and scattering, which both contribute to light attenuation. Using a series of diluted acrylate monomer miniemulsions ranging from 40 to 300 nm, all the methods converge toward a constant absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…S6) confirmed the increase of molecular weights of the formed block copolymers, indicating the successful secondary polymerization. The possible reason is that a certain amount of AIBN residuals are encapsulated in spherical micelles, which cannot be irradiated by UV light 28,29 to trigger 85 the polymerization. Furthermore, the successful thermal polymerization also indicated that the trithiocarbonate moieties in the system still had living character for further polymerization.…”
mentioning
confidence: 99%
“…S6) confirmed the increase of molecular weights of the formed block copolymers, indicating the successful secondary polymerization. The possible reason is that a certain amount of AIBN residuals are encapsulated in spherical micelles, which cannot be irradiated by UV light 28,29 to trigger 85 the polymerization. Furthermore, the successful thermal polymerization also indicated that the trithiocarbonate moieties in the system still had living character for further polymerization.…”
mentioning
confidence: 99%
“…[ 22 ] Scattering and absorption coeffi cients of acrylate miniemulsions were also determined in diluted [ 22 ] and concentrated [ 23 ] media using an integration sphere or the Kubelka-Munk theory, respectively. In this work, we employed a simple spectroscopic set-up to assess light penetration.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Beer–Lambert law, the absorbance ( A ) at wavelength λ can be expressed by Aλ=Eλ . l where E is the attenuation coefficient, l the optical path length. The attenuation coefficient can be separated into three components; the absorption coefficient from C4AzoTAB ( K C 4 AzoTAB ), the absorption coefficient from PSt particles (swollen with monomer in case of incomplete conversion) ( K PSt ) and the scattering coefficient from PSt particles ( S PSt ): E =KC4AzoTAB +KPSt+SPSt…”
Section: Methodsmentioning
confidence: 99%